The Use of E-Learning to Teach English in the Time of the Covid-19 Pandemic - Henny Mardiah (English Teaching and Linguistics Journal (ETLiJ), 2020)
ABSTRACTCorona (covid-19) pandemic that was claimed from Wuhan, China at the end of 2019 has transferred to countries over the world at the beginning of 2020. This pandemic has brought significant changes in every aspect of human life, economy or commerce, social, health, and education as well. The President of the Republic of Indonesia, Mr. Joko Widodo declared all Indonesian citizenships to practice social/physical distancing. Indonesian government took some preventive strategies to minimize the outbreak of COVID-19. In education sector, Indonesian Education and Culture Minister, Mr. Nadiem Anwar Makarim ordered all students including university students to study from home. This study aims to investigate the use of the E-learning as the current phenomenon in teaching English in the time of COVID-19 pandemic. This research was conducted with a descriptive qualitative research. The result of the study suggests that E-Learning system is considered as the one and only relevant teaching-learning method in the time of pandemic. Teachers and students just accessed the internet from homes and they would be connected to the E-learning application that has been approved by the institutions or the lecturers. However, challenges in applying E-learning were also undeniable, for instances: the unavailability of internet access/ WIFI, learners feel unmotivated, poor levels of student engagement. The lack of actual social and psychological interactions between teachers and students in E-learning system seemed to minimize affective domains. The interactive teacher-student talk is not as effective as in normal classroom. Supports from institutions (colleges or universities) and government are needed for the success of E-learning, particularly in the time of COVID-19 pandemic.